(untitled) (International Journal of Artificial Intelligence, Computer Science, Management and Technology, 2025)
The integration of the Internet of Things (IoT) in supply chain and management systems has significantly transformed traditional logistics and operational models into intelligent, data-driven ecosystems. This research explores the multifaceted applications of IoT in enhancing real-time tracking, predictive maintenance, inventory optimization, and sustainability across global supply networks. Employing both doctrinal (literature and statutory review) and non-doctrinal (case studies, market data, stakeholder insights) methodologies, the paper presents a comprehensive analysis of IoT-enabled efficiencies—such as Schneider Electric’s 18.7% delivery improvement and Amazon’s 40% fulfillment cost reduction—while also examining critical challenges, including cybersecurity risks, interoperability issues, and the high cost of adoption. Real-world deployments from 2023–2025 demonstrate how firms achieve measurable gains through strategic implementation of IoT, AI, blockchain, and edge computing. The findings underscore the urgent need for standardized protocols, collaborative frameworks, and sustainable governance models to realize the full potential of IoT in supply chain ecosystems. With the IoT-enabled logistics market projected to surpass USD 55 billion by 2031, the study advocates for adaptive strategies that align technological innovation with ethical practices, transparency, and resilience in future global supply networks.